The Concentration of Zn, Fe, Mn, Cu and Se in Fiber Fractions of Legumes in Indonesia - Evitayani, Evitayani; Warly, L (ANIMAL PRODUCTION, 2010)
This study was carried out to evaluate concentration of micro minerals (Zn, Fe, Mn, Cu and Se) of forages and their distribution in fiber fraction (neutral detergent fiber/NDF and acid detergent fiber/ADF) in West Sumatra during dry and rainy seasons. Four species of common legume namely Leucaena leucocephala, Centrocema pubescens, Calopogonium mucunoides and Acacia mangium were collected at native pasture during rainy and dry seasons. The results showed that micro minerals concentration of forages and their distribution in fiber fraction varied among species and season. In general, concentration of micro minerals was slightly higher in rainy season compared to dry season either in legumes forages. Data on legume forages showed that 75% of legumes were deficient in Zn and Mn, 62.5 % deficient in Cu and 50 % deficient in Se. There was no species of legume deficient in Fe. Distribution of micro minerals in NDF and ADF were also significantly affected by species and season and depends on the kinds of element measured. Generally, micro minerals were associated in fiber fractions and it yield much higher during dry season compared to rainy season. Iron (Fe) and selenium (Se) in forages were the highest elements associated in NDF and ADF, while the lowest was found in Copper (Cu). (Animal Production 12(2): 105-110 (2010)Keywords: Seasons, forages, micro mineral distribution, fiber fraction